2005
DOI: 10.1002/bit.20440
|View full text |Cite
|
Sign up to set email alerts
|

High‐efficiency protein expression mediated by enterovirus 71 internal ribosome entry site

Abstract: An internal ribosome entry site (IRES) has been used to facilitate the expression of more than one protein in a single transcript. In this study, we examined the translational activities of several IRES elements derived from different RNA viruses. The protein expression of encephalomyocarditis virus (EMCV) IRES is similar to that of hepatitis C virus (HCV) IRES in mammalian cells. Notably, the protein expression of enterovirus 71 (EV71) IRES was 23-fold higher than the efficiency of EMCV IRES following normali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…The HEV71 genome is uncapped and viral protein translation is initiated via an IRES [82]. The secondary structure of the IRES is essential for translation, and the IRES is thought to interact with the 40S ribosomal subunit either directly or via host cell factors [82][83][84].…”
Section: Viral Protein Translationmentioning
confidence: 99%
“…The HEV71 genome is uncapped and viral protein translation is initiated via an IRES [82]. The secondary structure of the IRES is essential for translation, and the IRES is thought to interact with the 40S ribosomal subunit either directly or via host cell factors [82][83][84].…”
Section: Viral Protein Translationmentioning
confidence: 99%
“…We generated the plasmids pGS-EV71 and pGS-EMCV as described by Lee et al [19] . These contained IRES elements derived from EV71 and EMCV, respectively, flanked by the β-galactosidase as well as secreted alkaline phosphatase (SEAP) reporter genes.…”
Section: Methodsmentioning
confidence: 99%
“…However, EMCV IRES-mediated translation is less efficient than the cap-dependent translation of the upstream gene [17,18] . We have previously reported a potent IRES derived from the picornavirus Enterovirus 71 (EV71) and demonstrated the EV71 IRES translation efficiency to be approximately 10-to 15-fold higher than that of EMCV IRES in cell lines [19] . In this study, we identified amantadine, a compound that inhibited EV71 IRES as well as EMCV IRES-mediated translation but did not interfere with cap-dependent translation.…”
Section: Introductionmentioning
confidence: 99%
“…The SEAP gene was then inframed-fused with the EGFP gene in the pBacDRhirE plasmid. Briefly, the SEAP gene fragment was first amplified from the pGS-HCV plasmid (Lee et al 2005) by polymerase chain reaction (PCR) with the forward primer, 5¢-AT ATAAGATCTCCACCATGCTGCTGCTGTG CTGCTGCTGGG-3¢ (with the BalII site underlined), and the reverse primer, 5¢-AATTCAG ATCTGGTGTCTGCTCGAAGCGGCCGGC-3¢ (with the BalII site underlined). Two GG nucleotides in the reverse primer (bold and italicized) were added to allow the in-frame fusion between the 3¢ end of the SEAP and the 5¢ end of the EGFP gene.…”
Section: Construction Of Plasmid Transfer Vectorsmentioning
confidence: 99%